Si-RF Technology - Karmakar, Ayan.; Singh, Kamaljeet; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the recent research developments of various passive microwave circuits on silicon substrate and demonstrated operations catering for multiple frequency bands. It covers the design, modelling, process fabrication and characterization aspects with practical examples. The book will be of use to researchers and engineers working in the field of RF or microwave engineering, who can use the techniques and approaches effectively without having to refer to multiple sources. .
Chapter 1: Silicon implementation of Planar Topologies -- Chapter-2: Fabrication technologies -- Chapter 3: Passive Circuits -- Chapter-4: Planar Antenna -- Chapter-5: MEMS Switch -- Chapter-6: Packaging concept in Radio Frequency -- Appendix-1: Material properties of some useful metals and dielectrics -- Appendix 2: Relaxation time estimation for some materials used in RF/microwave applications -- Appendix 3: Etch rate of various thin films of in wet and dry method -- Appendix 4: Readymade Chart for VSWR, Return Loss and Reflection Coefficient.
Keywords: Telecommunication; Electronic circuits; Optical materials; Wireless communication systems; Mobile communication systems; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Optical Materials; Wireless and Mobile Communication